Non Stop Educational Support: Exploring the Opportunities and Challenges of Intelligent Chatbots Use to Support Learners from the Viewpoint of Practitioner Educators - Alsayed , Wael Omar; Al-Hafdi , Fahad Saleem; Alhalafawy , Waleed Salim (Journal of Ecohumanism, 2024)
Chatbots use in education is still in need for the identification of opportunities resulting from their use as well as the challenges facing the expansion of such use despite the massive spread of these Chatbots recently. The merits of Chatbots have prompted some teachers to use them to provide learners' with educational support, which consequently helped the appearance of a group of teachers who start practice using Chatbots techniques in education. Therefore, the present study aims to identify the viewpoints of practitioner teachers regarding the opportunities and challenges of Chatbots use in providing learners with educational support. The phenomenological approach is used via conducting Semi-structured interviews with practitioner teachers, five main motivating questions were used to generate the data. Participants were (11) teachers who were purposefully selected from the practitioner teachers who were using Chatbots to provide support services in the primary, middle and secondary educational levels. The results showed that Chatbots in education provide many opportunities that contribute to increasing the efficiency of the educational support through flexibility of support, motivation, accessibility and availability, in addition to guidance and counseling processes. This study also revealed a number of physical, technical and ethical challenges in front of using this technology in providing educational support.